Whole-genome resource sequences of 57 indigenous Ethiopian goats - Belay, Shumuye; Belay, Gurja; Nigussie, Helen; Jianlin, Han; Tijjani, Abdulfatai; Ahbara, Abulgasim; Mekuriaw, Getinet; Woldekiros, Helina S.; Mor, Siobhan M.; Dobney, Keith; Lebrasseur, Ophelie; Hanotte, Olivier H.; et al. (Springer, 2024)
Domestic goats are distributed worldwide, with approximately 35% of the one billion world goat population occurring in Africa. Ethiopia has 52.5 million goats, ~99.9% of which are considered indigenous landraces deriving from animals introduced to the Horn of Africa in the distant past by nomadic herders. They have continued to be managed by smallholder farmers and semi-mobile pastoralists throughout the region. We report here 57 goat genomes from 12 Ethiopian goat populations sampled from different agro-climates. The data were generated through sequencing DNA samples on the Illumina NovaSeq 6000 platform at a mean depth of 9.71x and 150 bp pair-end reads. In total, ~2 terabytes of raw data were generated, and 99.8% of the clean reads mapped successfully against the goat reference genome assembly at a coverage of 99.6%. About 24.76 million SNPs were generated. These SNPs can be used to study the population structure and genome dynamics of goats at the country, regional, and global levels to shed light on the species’ evolutionary trajectory.